2008
DOI: 10.1080/01635580701649644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colonic Bacterial Metabolites on Caco-2 Cell Paracellular Permeability In Vitro

Abstract: One common effect of tumor promoters is increased tight junction (TJ) permeability. TJs are responsible for paracellular permeability and integrity of the barrier function. Occludin is one of the main proteins responsible for TJ structure. This study tested the effects of physiological levels of phenol, ammonia, primary bile acids (cholic acid, CA, and chenodeoxycholic acid, CDCA), and secondary bile acids (lithocholic acid, LCA, and deoxycholic acid, DCA) on paracellular permeability using a Caco-2 cell model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 30 publications
3
71
0
Order By: Relevance
“…Protein fermentation is less studied than carbohydrates; however, it has been suggested that branched-chain fatty acids (BCFAs) and other products coming from protein fermentation, such as ammonia, phenols, amines, and sulfides, could affect the viability of colonocytes [43]. PICRUSt analysis predicted higher amino acid metabolism in the RTT group, which is in line with the higher protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…Protein fermentation is less studied than carbohydrates; however, it has been suggested that branched-chain fatty acids (BCFAs) and other products coming from protein fermentation, such as ammonia, phenols, amines, and sulfides, could affect the viability of colonocytes [43]. PICRUSt analysis predicted higher amino acid metabolism in the RTT group, which is in line with the higher protein intake.…”
Section: Discussionmentioning
confidence: 99%
“…Transepithelial resistance of Caco-2 cells was decreased after incubation with NH 3 (10-100 mM), phenol (1-10 mM) and both primary and secondary bile acids (50-250 mM) [34]. McCall et al confirmed the effect of phenol on cell permeability in SK-CO15 cells, which are also transformed human intestinal epithelial cells.…”
Section: P-cresol and Phenolmentioning
confidence: 90%
“…Recently, H 2 S has been proposed to destabilize the mucus layer through disulfide bond reduction [72,73], therefore possibly facilitating the contact of luminal compounds with the colonic mucosa. The AA-derived microbial metabolites phenol and ammonia have been found to increase epithelial permeability [74], while indole and branched-chain fatty acids have shown protective effects on this intestinal parameter [75,76,77]. Among AA-derived bacterial metabolites, ammonia and H 2 S have been shown to induce the expression of pro-inflammatory genes in colonic IEC [50,65] while indole and related compounds exert immuno-regulatory effects [75,76,78,79].…”
Section: Potential Role Of Dietary Proteins In Inflammatory Flarementioning
confidence: 99%